Learners’ Engagement and Perception on Corrective Feedback of Online Tools Towards Students’ Essay Writing in EFL Context - Muh Junaidi; Muh Hisbullah; M. Imam Burhanudin; Baiq Siti Aulia Hovia; Abdul Azizurrohman (Humanitatis : Journal of Language and Literature, 2022)
Written, oral and online corrective feedback have become interesting topic for developing learners’ writing skills in a second or foreign language context. The study aims at discovering the correlation between Learners’ engagement and perception on the use of online tools towards Students’ writing. Determining students perception on online CF was also the main concern. Multiple correlation used for analyzing data collected from 150 respondents through questionnaires and academic writing test. The study reveals that coefficient correlation between learners’ Engagement and perception. is .996 and significant value 2-tailed is .000, which is greater than p-value .05. Furthermore, The Sig value of F change is.000, lower than the 0.05 p-value threshold; the value R.996 which is higher than sig. 0.05. Hence, it is a considerable and an extremely high degree association between students' level of involvement and perceptions of students' essay writing abilities. Values of students’ perception in percentage distribution indicate the preference of online CF in terms of perceived usefulness, ease of use, self-efficacy and behavioral intention. Further study may concern on multifactorial analysis for providing more comprehensive study.